Shaping science: Scholarly motivation and research outcomes in NIH-HEAL funded studies - Bryce Kushmerick-McCune; Ginnie Sawyer-Morris; Merve Ulukaya; Kendra Clark; Scott T. Walters; Faye S. Taxman (PLoS ONE, 2026)
In 2018, the National Institutes of Health (NIH) launched the Helping to End Addiction Long-Term ® (HEAL) Initiative to advance addiction and pain research and clinical practice. The NIH-HEAL Initiative supports investigator-initiated research across diverse focus areas, allowing scientists discretion in selecting research topics, methodologies, and outcomes while still remaining subject to NIH’s peer review process. This study aims to answer the research question: what do investigators of NIH-HEAL funded studies define as important knowledge, particularly in relation to growth in empirical studies and clinical policy? By examining how pain and addiction researchers define what knowledge is important to produce, this study offers novel insight into how research priorities take shape and why this matters for science and clinical practice. To answer this research question, we conducted a directed content analysis of 1,068 NIH-HEAL funded study abstracts published on the NIH RePORTER website. Our findings suggest that while the scope of the NIH-HEAL funded studies is broad, there are common identifiable patterns that exist within the funded research portfolio such as a preference for treating pain and addiction conditions with prescription medication (33.80% of pain studies, 34.17% of opioid use disorder studies) and a narrow focus on intervention efficacy (43.21% of pain studies, 39.22% of opioid use disorder studies). This analysis is important for the scientific enterprise and clinical practice as prior literature has painted research as inherently influenced by the values of a scientist and of their discipline. By identifying what social and empirical problems NIH-HEAL funded investigators identify, their proposed solutions, and the outcomes they prioritize, this study carries important implications for grant-funding agencies, scientists, and the people who need and receive treatment for pain and addiction conditions.